Influência dos sintomas depressivos maternos no desenvolvimento infantil: 12 meses de seguimento - Calixto, Andressa Furtado (2018)
Background: The depression is one of the most common complications of pre and postpartum periods, which can have negative consequences for both the woman and the child as well as the family. Postpartum depression (PPD) losses to the child may be associated with cognitive impairment, emotional impairment, and maladaptive patterns of behavior. However, there are few studies addressing the effects of PPD symptoms on child development over time, especially with borderline term and preterm infants. Objective: To evaluate the child development of daughters of mothers who presented scores compatible with maternal depressive symptoms, from the second to the twelfth month after birth. Method: Prospective cohort study, conducted in Brazil, with the participation of 160 mothers and their children. To identify the symptoms of PPD, the mothers responded to the Edinburgh Postnatal Depression Scale (EPDS) at 2 and 9 months postpartum. It was considered as a presence of PPD symptoms when, in at least one of the measures, the score was equal to or greater than 10. For the evaluation of the child development, Bayley Scales of Infant and Toddler Development III (Bayley III) at 2, 4, 6, 9, 12 months of age. All participants answered the questionnaires structured with maternal, perinatal and socioeconomic data. For the data analysis, we used Generalized Equations Estimating (GEE), Generalized Linear Models (GLM) and, later, linear and logistic regressions. Results: It was observed that 37.5% of the mothers who responded to the EPDS had symptoms of PPD in at least one of the evaluated moments. It was possible to verify the association between PPD symptoms and child development, specifically in fine motor skills, at 9 (p = 0.020) and at 12 (p = 0.009) months. The symptoms of PPD had no significant association to the Bayley subscales of cognitive, language (receptive and expressive) and gross motor. Conclusion: Children of mothers with PPD symptoms presented alterations in child development, specifically in fine motor skills at 9 and 12 months of age in relation to the children of mothers without symptoms of PPD.